2012
DOI: 10.1186/1741-7007-10-11
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic wasp responses to symbiont-based defense in aphids

Abstract: Background Recent findings indicate that several insect lineages receive protection against particular natural enemies through infection with heritable symbionts, but little is yet known about whether enemies are able to discriminate and respond to symbiont-based defense. The pea aphid, Acyrthosiphon pisum , receives protection against the parasitic wasp, Aphidius ervi , when infected with the bacterial symbiont Hamiltonella defen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(92 citation statements)
references
References 66 publications
(80 reference statements)
3
86
1
Order By: Relevance
“…Discrepancy between aphid hospitality to the A. ervi wasp vs. hospitality to its progeny, where extra eggs are invested to balance immature mortality, is an important finding that emerges from this study (see also [33] who independently observed the same mechanism). In order to exploit a ‘multifaceted’ polymorphic and clonally reproducing host such as A. pisum , the A. ervi wasps and immatures must balance their differential capacity to use hosts with divergent hospitality occurring together in mixed host populations.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Discrepancy between aphid hospitality to the A. ervi wasp vs. hospitality to its progeny, where extra eggs are invested to balance immature mortality, is an important finding that emerges from this study (see also [33] who independently observed the same mechanism). In order to exploit a ‘multifaceted’ polymorphic and clonally reproducing host such as A. pisum , the A. ervi wasps and immatures must balance their differential capacity to use hosts with divergent hospitality occurring together in mixed host populations.…”
Section: Discussionsupporting
confidence: 54%
“…Host susceptibility to A. ervi in A. pisum is clonally variable, depending behaviorally on aphid body color ([29] and references therein), and physiologically on host defensive anti-parasitoid bacterial symbionts. In particular, Hamiltonella defensa bacteria can kill or stop development of A. ervi immature stages, thus acting as a symbiotic form of host resistance (reviewed in [30]; see also [29], [31], [32], [33]). With host defensive bacteria, the Aphidius -aphid host system thus comprises three players associated in a tripartite trophic, symbiotic, and parasitic interaction.…”
Section: Introductionmentioning
confidence: 99%
“…[25,40,41]). It is possible that the parasitoid exhibited different oviposition behavior in the different treatments, but typically this is observed in choice rather than no-choice assays [25,40,42,43]. …”
Section: Methodsmentioning
confidence: 99%
“…Aphids are thus ideal experimental models to understand the impact of defensive symbionts on the evolution of their hosts and parasites. For instance, it is employed to study the cost of defensive symbionts (Vorburger et al, 2013; Polin et al, 2014; Cayetano et al, 2015), their population dynamics (Oliver et al, 2008), their role in parasitoid community composition (Rothacher et al, 2016), the specificity of symbiont-associated defense (Martinez et al, 2016b), and to demonstrate that host symbiont’s role in defense imposes new selection pressure on parasites (Oliver et al, 2012). Another biological system worth mentioning is the role of Wolbachia against viruses.…”
Section: Host Defensive Symbiontsmentioning
confidence: 99%